2004
DOI: 10.1161/01.cir.0000140973.60992.9a
|View full text |Cite
|
Sign up to set email alerts
|

Increased Collagen Type I Synthesis in Patients With Heart Failure of Hypertensive Origin

Abstract: Background-We investigated whether increased collagen type I synthesis and deposition contribute to enhancement of myocardial fibrosis and deterioration of cardiac function in patients with hypertensive heart disease (HHD). Methods and Results-We studied 65 hypertensives with left ventricular hypertrophy subdivided into 2 groups: 34 patients without heart failure (HF) and 31 patients with HF. Transvenous endomyocardial biopsies of the interventricular septum were performed to quantify the amount of fibrotic ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
186
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 397 publications
(200 citation statements)
references
References 33 publications
8
186
2
4
Order By: Relevance
“…16 Higher levels of PICP were recently reported in hypertensives with than in those without heart failure. 17 Markedly elevated baseline PICP levels in our study indicated that significant fibrosis was present in our elderly with diastolic dysfunction. After 4 months of treatment with spironolactone, PICP levels decreased significantly from baseline values.…”
Section: Discussionmentioning
confidence: 47%
“…16 Higher levels of PICP were recently reported in hypertensives with than in those without heart failure. 17 Markedly elevated baseline PICP levels in our study indicated that significant fibrosis was present in our elderly with diastolic dysfunction. After 4 months of treatment with spironolactone, PICP levels decreased significantly from baseline values.…”
Section: Discussionmentioning
confidence: 47%
“…Those situations can be associate to impaired degradation of collagen type I. Conformational changes of this protein also occur in people with heart failure. As a result of proteins modification, increasing of collagen type I content is observed [40], What lead to change of tissue stiffness? It is worth mentioning that in arterial vessels, protein structure also can be altered during pathological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The above considerations allow to conclude that stiffness tissue modification are not one-way process. In the case of the heart, the liver or even abnormal wound healing, the impaired function of the degradation can be the reason [38][39][40]. However, skin diseases modifications of lipid conformations can be the source of problems.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] This excess of myocardial collagen is primarily a result of the uncoupling between increased synthesis and unchanged or decreased degradation of collagen type I fibres. 18 However, patients with coronary heart disease have been excluded from these studies, 11-14 so it is not clear if a different pattern of interstitial remodelling may be present in the first months after AMI in patients with antecedent hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] Accordingly, we serially measured serum products collagen types I and III turnover, which constitute the bulk of cardiac ECCM, 15 and LV volumes and function in a consecutive sample of patients successfully treated with primary percuta-neous coronary intervention (PCI) for a first AMI with LV systolic dysfunction. The purpose of this study was to evaluate if a different pattern of ECCM and LV remodelling is present in patients with antecedent hypertension compared with those without hypertension.…”
Section: Introductionmentioning
confidence: 99%